2020
DOI: 10.1039/d0sc02881a
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic three-component C–C bond forming dearomatization of bromoarenes with malonates and diazo compounds

Abstract: A Pd-catalyzed dearomative three-component C–C bond formation of bromoarenes with diazo compounds and malonates was developed. Various bromoarenes ranging from benzenoids to azines and heteroles were transformed to the corresponding...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Very recently, the same group also developed palladiumcatalyzed three-component dearomatization/alkylation reaction of bromoarenes with diazo compounds and malonates to furnish substituted alicyclic products (Scheme 29). [36] Under the optimized conditions, substituted six-membered bromoarenes reacted smoothly to produce 1,4-and 1,2-difunctionalized alicyclic molecules in good to high yields. In addition, the reaction was suitable for a variety of heterocyclic aryl bromides including azines and heteroles.…”
Section: Formation Of Benzylpalladium Intermediates Via Palladiumà Carbene Migratory Insertionmentioning
confidence: 98%
“…Very recently, the same group also developed palladiumcatalyzed three-component dearomatization/alkylation reaction of bromoarenes with diazo compounds and malonates to furnish substituted alicyclic products (Scheme 29). [36] Under the optimized conditions, substituted six-membered bromoarenes reacted smoothly to produce 1,4-and 1,2-difunctionalized alicyclic molecules in good to high yields. In addition, the reaction was suitable for a variety of heterocyclic aryl bromides including azines and heteroles.…”
Section: Formation Of Benzylpalladium Intermediates Via Palladiumà Carbene Migratory Insertionmentioning
confidence: 98%
“…Moreover, aryl N ‐tosylhydrazones can be used in the transformation instead of TMS‐diazomethane (Scheme 20). [44] …”
Section: The Formation Of C−c Bonds Via Benzyl Palladium Intermediatementioning
confidence: 99%
“… 16 Then Yamaguchi et al reported the dearomative allylation of benzyl phosphates with allyl borates, 17 as well as a series of beautiful dearomative three component reactions of haloarenes, in which the π-benzyl complex is generated by the Pd-catalyzed insertion of diazo-compounds. 18 Interestingly, nitrogen based as well as malonates and arylacetonitriles based nucleophiles were also reported to support addition to the π-benzyl intermediate, 19,20 although most protocols require subsequent in situ rearomatisation of the formed semibenzene to achieve good conversions. All of these methodologies result in good yields; however, the low reactivity of the reported nucleophiles give rise to longer reaction times (12–24 h) and typically necessitate a relatively high catalyst loading, specific phosphine-ligands and high temperatures.…”
mentioning
confidence: 99%